Marketing Strategy of Local Products through Social Media in Segara Jaya Village - Andrian Haro; Agung A. W. S. Waspodo; Friska Aviyati Lestari; Cindy (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2020)
To introduce local products made by the community, it is necessary to conduct training on effective and efficient strategies in marketing products through social media. The purpose of this training is to motivate and educate the community in managing their businesses by using social media marketing. This training uses demo and counseling method which is participated by 30 participants. Participants are given motivation and introduction to social media marketing (i.e. Facebook, Twitter, Instagram, and e-commerce like Shopee, Tokopedia, and Bukalapak) that could facilitate them in promoting their local products with several marketing strategies. The target of this training is the participants able to market and to sell their local products online with social media. Also, the existence of interactive social media training is expected that the community to create greater and more developed business opportunities toward their local products. These conditions will certainly have a positive impact on increasing their business revenues in the future.